2021
DOI: 10.1111/cob.12506
|View full text |Cite
|
Sign up to set email alerts
|

Heart valve surgery and the obesity paradox: A systematic review

Abstract: Obesity has been associated with increased incidence of comorbidities and shorter life expectancy, and it has generally been assumed that patients with obesity should have inferior outcomes after surgery. Previous literature has often demonstrated equivalent or even improved rates of mortality after cardiac surgery when compared to their lower-weight counterparts, coined the obesity paradox. Herein, we aim to review the literature investigating the impact of obesity on surgical valve interventions. PubMed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 71 publications
1
14
0
5
Order By: Relevance
“…Evidence from clinical cohorts of patients with cardiovascular disease suggests that the obesity paradox lies in the fact that overweight and obese patients with cardiovascular disease appear to have a better short-term and long-term prognosis than lean patients. In recent years, several studies have suggested that obese patients may be at no different risk for cardiac surgery than non-obese patients, particularly in terms of mortality [5][6][7]. This study found that overweight and obese patients had a signi cantly increased risk of CSA-AKI after surgery, in contrast to the cardioobesity paradox, consistent with previous studies [28,29].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Evidence from clinical cohorts of patients with cardiovascular disease suggests that the obesity paradox lies in the fact that overweight and obese patients with cardiovascular disease appear to have a better short-term and long-term prognosis than lean patients. In recent years, several studies have suggested that obese patients may be at no different risk for cardiac surgery than non-obese patients, particularly in terms of mortality [5][6][7]. This study found that overweight and obese patients had a signi cantly increased risk of CSA-AKI after surgery, in contrast to the cardioobesity paradox, consistent with previous studies [28,29].…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, several studies have suggested that obese patients may be at no different risk for cardiac surgery than non-obese patients, particularly in terms of mortality [5][6][7]. However, these studies are limited by single-center, small-sample studies.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, BMI was inversely correlated with mortality. This latter concept is known as 'obesity paradox' and has been described already by others (13,14).…”
Section: Discussionmentioning
confidence: 76%
“…Visceral obesity causes a decrease in insulinmediated glucose uptake, insulin resistance and ultimately endothelial dysfunction (3,5). Nonetheless, waist circumference is seldom measured in the cardiac surgery context, and most studies that investigated the obesity paradox have considered the BMI as measure of obesity, rather than waist circumference (14).…”
Section: Discussionmentioning
confidence: 99%
“…This latter concept is known as "obesity paradox" and has been described already by others. 12,13 Nevertheless, there are two important considerations to be made for "obesity": the first is that not always obesity is synonymous of MetS since there are so-called metabolically healthy obese (MHO) individuals with high level of insulin sensitivity without systemic hypertension and atherogenic dyslipidaemia and other features of MetS. 14,15 A survey analysis, suggested that MHO may account for a significant percentage of obese population.…”
Section: Discussionmentioning
confidence: 99%